Identification of metabolic syndrome in patients with diabetes mellitus and hypertension - Josefa Bell Castillo; Wilberto George Carrión; María Eugenia García Céspedes; Evelyn Delgado Bell; María de Jesús George Bell (Centro Provincial de Información de Ciencias Médicas, 2017)
A descriptive, observational and cross-sectional study of 93 hypertensive and diabetic patients with metabolic syndrome association was carried out, who were admitted to the Internal Medicine wards in "Dr. Juan Bruno Zayas Alfonso" Teaching General Hospital from Santiago de Cuba during 2015-2016, aimed at characterizing them according to some clinical, imagenological and humoral variables. In the series there was a prevalence of female sex (61.0%) and 55-64 age group (36.5%), as for complications as well as radiological and humoral parameters evaluated, were directly related to timecourse of the diseases, likewise there was a higher number of deaths due to ischemic heart disease (55.0%). It was concluded that there is a higher lack of control in patients with this syndrome from the humoral and imagenological point of view with proportional efect to the disease timecourse and a consequent development of cardiovascular, renal and cerebrovascular complications, that can even lead to death.